(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
The objective of this study was to develop an original anti-bacterial material for skin wound healing. Collagen-chitosan nanofibrous membranes were fabricated by electrospinning. The morphology, tensile strength and contact angle of the membranes were measured. In addition, cell adhesion and proliferation on the membranes were evaluated. The antimicrobial property against Staphylococcus aureus of the membranes was also determined. The results indicated that the diameter of electrospun collagen-chitosan nanofibrous membranes was 221 ± 105 nm, the tensile strength was 1.53 ± 0.12 Mpa and the contact angle was 42.44 ± 4.03 ° . Besides, the collagen-chitosan nanofibrous membranes promoted cell attachment and proliferation and also inhibited the growth of Staphylococcus aureus. In conclusion, these data suggest that electrospun collagen-chitosan nanofibrous membranes have potential to serve as skin wound healing materials, which might be ascribed to its favorable mechanical strength, excellent cell affinity, as well as good antimicrobial properties against Staphylococcus aureus.